Overview Of Land Facilities At Bahaur Ferry Port In Pulang Pisau Central Kalimantan Province - Driaskoro Budi Sidharta; Miran Miran (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2023)
Bahaur Ferry Port is a port located in Pulang Pisau Regency, Central Kalimantan Province and then managed by the Central Kalimantan Provincial Transportation Service and supervised by the Land Transportation Management Center (BPTD) Region XVI Central Kalimantan Province. There are still some deviations in port operations in terms of the Minister of Transportation KM. 52 of 2004, such as waiting rooms, inadequate offices due to joining ticket sales, and ready-to-load parking spaces that join the delivery/pick-up vehicle parking lots make the delivery/pick-up vehicles park their vehicles in any place because the parking lot is filled with ready-to-eat vehicles. fit. In addition, the Bahaur Ferry Port does not yet have a weighbridge and vehicle height limiter facilities. For this reason, it is necessary to review the fulfillment of the need for land facilities at the Bahaur Ferry Port. The method used to analyze the existing problems is the analysis of the calculation of the area needs based on KM. 52 of 2004 concerning the Operation of Ferry Ports and PM. 103 of 2017 concerning Regulation and Control of Vehicles using Crossing Transportation Services. Based on this analysis, it can be concluded that the land facilities at the Bahaur Ferry Port have not provided optimal services, so it is necessary to increase the area of the terminal building and the ready-to-load parking area as well as the parking area for delivery/pick-up vehicles and the procurement of a weighbridge and vehicle height limiter.